Respuesta :
Answer:
s /2 pi r - r = h
Step-by-step explanation:
s = 2 pi r ( r+h)
Divide each side by 2 pi r
s /2 pi r = 2 pi r ( r+h) / 2 pi r
s /2 pi r = ( r+h)
Subtract r from each side
s /2 pi r - r = ( r+h) -r
s /2 pi r - r = h
Answer:
[tex] h = \frac{s}{2\pi \: r} - r \\ [/tex]
Step-by-step explanation:
[tex]s = 2\pi \: r(r + h) \\ \frac{s}{2\pi \: r} = \frac{2\pi \: r(r + h)}{2\pi \: r} \\ \frac{s}{2\pi \: r} = r + h \\ \frac{s}{2\pi \: r} - r = h[/tex]
hope this helps
brainliest appreciated
good luck! have a nice day!